Tumor-infiltrating lymphocytes provides recent survival information for early-stage HER2-low-positive breast cancer: a large cohort retrospective study - Sun, Teng; Wang, Tong; Li, Xiangjun; Wang, Haibo; Mao, Yan (Frontiers in Oncology, 2023)
Purpose It has been reported that breast cancer (BC) with low expression of Human epidermal growth factor receptor 2 (HER2) might be a distinct subtype of breast cancer. But the prognostic effect of low HER2 expression on BC patients remains controversial. We aim to conduct this single-institution retrospective analysis to assess the HER2-low-positive BC outcomes in China women and the prognostic role of TILs in HER2-low-positive with early-stage BC. Method We totally retrospectively enrolled 1763 BC patients treated by a single institution from 2017 to 2018. TILs are regarded as continuous variables and are divided into low TILs (≤10%) and high TILs (>10%) for statistical analysis. Univariate and multivariable Cox proportional hazards regression model were used to test the associations between TILs and disease-free survival (DFS) with the adjustment for clinicopathologic characteristics. Result High TILs level (>10%) were associated with tumor size (>2cm, p=0.042), age at diagnosis (p=0.005), Ki-67 index (>25%; p<0.001), HR status (positive, p<0.001), advanced pathological stage (p=0.043), subtypes (p<0.001) and HER2 status (p<0.001). Kaplan-Meier analysis indicated that no significant difference of DFS (p=0.83) could be found between HER2 positive, HER2-low-positive and HER2-0 BC. DFS of HER2-low-positive BC and HER2-nonamplified BC with high levels of TILs was statistically better than presented a low levels of TILs (p=0.015; p=0.047). In HER2-low-positive BC patients with high TILs level (>10%) the DFS was significantly improved in both univariate (HR=0.44, 95% CI 0.22-0.87, P=0.018) and multivariate (HR=0.47, 95% CI 0.23-0.95, P=0.035) Cox models. For further subgroup analysis, the HR (+)/HER2-low-positive BC with high TILs (>10%) level was associated with improved DFS in both univariate (HR=0.41, 95% CI 0.19-0.90, P=0.025) and multivariate (HR=0.42, 95% CI 0.19-0.93, P=0.032) Cox models. The HR (-)/HER2-0 BC with high TILs (>10%) level was not statistically significant in the univariate Cox model, but it was statistically significantly in the multivariate (HR=0.16, 95% CI 0.28-0.96, P=0.045) Cox model. Conclusion Among early stage breast cancer, no significant survival difference could be found between HER2 positive, HER2-low positive and HER2-0 cohort. The high levels of TILs were significantly associated with improved DFS in HER2-low-positive patients, especially in the HR (+)/HER2-low-positive subtype.